Analisis Implementatasi Strategi Bauran Pemasaran 7P Pada Usaha Bakso Wong Jowo By Tiwi - Pratiwie Nirmala Dewi; Chandra Hendriyani; Rommy Mochammad Ramdhani (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2021)
Abstract: The purpose of this research is to study how the implementation of the marketing mix strategy in the Bakso Wong Jowo By Tiwi business. The current global pandemic, namely Coronavirus Disease (Covid-19), hampers all community activities. The social distancing system that is implemented to minimize the spread of virus transmission, on the other hand has a negative impact. One of the elements most affected by the social distancing system is the labor. Many workers who are dismissed are even laid off (Termination of Employment) due to decreased company activities. Cause of that, the community is expected to be more creative and innovative person in order to survive in fulfilling their daily needs, especially in this pandemic era. One of the ways is making UKM (Usaha Kecil Menengah) which can be done at home by utilizing existing technology. Bakso is a typical Indonesian culinary delicacy that is very much in demand by the public, especially in Cimahi City. Bakso Wong Jowo By Tiwi is a type of UKM that is engaged in home-made culinary (Homemade) with the Javanese slogan